2019
DOI: 10.4103/ijd.ijd_490_18
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis in adults and irritable bowel syndrome: A cross-sectional study

Abstract: Background:Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disorder affecting a large number of people in the world. Atopic dermatitis (AD) is a common inflammatory skin condition characterized by relapsing eczematous lesions in a typical distribution. It was first described in 1933 but exists since antiquity.Aim and Objectives:To determine the relationship between AD and IBS.Materials and Methods:A total of 109 patients with AD and 100 healthy controls were included in the study. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…However, since the exact prevalence of each of the diagnoses included in the visual impairment EDC was unavailable, we were unable to contrast their results with our own. Our results for irritable bowel syndrome (1.90 (1.56-2.31)) were consistent with other recently published studies on children and adults with AD [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…However, since the exact prevalence of each of the diagnoses included in the visual impairment EDC was unavailable, we were unable to contrast their results with our own. Our results for irritable bowel syndrome (1.90 (1.56-2.31)) were consistent with other recently published studies on children and adults with AD [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…However, there are conflicting results depending on studies. 4 Some reports found significant higher prevalence of IBS in atopic dermatitis (AD) patients compared with controls 5 and higher risk to develop IBS in children suffering from AD. 6 On the other hand, atopic disease was found to be slightly increased in patients with IBS compared to control but without reaching statistical significance.…”
mentioning
confidence: 99%
“…Recently, atopic diseases have been reported to be associated with functional GI disorders such as functional dyspepsia and irritable bowel syndrome [ 15 ]. Moreover, adults with AD had higher odds of developing gastroenteritis than those without AD [ 33 , 34 ]. In this study, we found the GI function such as dyspepsia and gastric discomfort correlated with AD symptoms (SCORAD).…”
Section: Discussionmentioning
confidence: 99%